Intimate Partner and Family Violence Among Women Tertiary Students in Australia: Prevalence and Cross-Cultural Differences - Zark, Laura (Violence against women, 2024)
Most prior research on violence among tertiary students has been restricted to dating and sexual violence and neglected cross-cultural variation. To provide more comprehensive and intersectional understandings, this study examined the prevalence and cultural differences in intimate partner and family violence among women tertiary students in Australia. Data were collected from 1,845 women studying at post-secondary institutions and weighted by age and country of birth to reflect the population composition. Eighty-seven percent (86.7%) of participants reported having experienced violence (physical, sexual, psychological, and/or financial) from an intimate partner and/or family member during adulthood. Students who identified as Anglo were more likely to report victimization by intimate partners, while those who identified as non-Anglo and multicultural were more likely to report victimization by family members. The findings highlight the need for tertiary education institutions to prioritize preventing and responding to intimate partner and family violence in their culturally diverse student bodies.